Adaptive model-parameter-free fault-tolerant trajectory tracking control for autonomous underwater vehicles. (August 2021) - Zhu, Cheng; Huang, Bing; Zhou, Bin; Su, Yumin; Zhang, Enhua
Abstract: This paper provides a model-parameter-free control strategy for the trajectory tracking problem of the autonomous underwater vehicle exposed to external disturbances and actuator failures. Two control architectures have been constructed such that the system states could be forced to the desired trajectories with acceptable performance. By combining sliding mode control (SMC) technology and adaptive algorithm, the first control architecture is developed for tracking missions under healthy actuators. Taking actuator failures scenario into account, system reliability is improved considerably by the utilization of a passive fault-tolerant technology in the second controller. Benefitting from properties of Euler–Lagrange systems, the nonlinear dynamics of the underwater vehicles could be handled properly such that the proposed controllers could be developed without model parameters. Finally, the validity of the proposed controllers is demonstrated by theoretical analysis and numerical simulations. Highlights: Two model-parameter-free tracking controllers are developed for AUVs. With proper transformation, actuator faults could be accommodated with satisfactory performance. The proposed methods possess the properties of high simplicity and intuitiveness.